Empirisk forskning om domstolar i Finland - Mika Sutela (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract The subject of my article-based dissertation in law was decision-making in the general courts of Finland. My research aimed to describe how uniform decisionmaking is in the Finnish courts. With regard to district courts convictions of aggravated drunk driving were the main focus of my study. The results show that there are regional differences in the sentences. Results are based on empirical legal research that draws on aspects of criminal and procedural law as well as criminology. Prior to this, only a few empirical studies had been conducted in Finland that focused on the courts and other criminal sanctioning systems. In the current dissertation, the equality and predictability of judicial decision-making act as theoretical starting points. The dissertation adopts a research tradition established at the international level where the influence of legal and extra-legal factors, e.g., offender age, on sentencing is explored. At a more theoretical level, the dissertation reflects the research tradition of legal realism. Empirical legal research will play an increasingly important role in the future. It can increase both equality before the law, as well as the transparency of decision-making and confidence in the judicial process. Data on, e.g., punishments meted out by the courts, should be kept as current as possible since information on the functioning of the legal system is important. Empirical court research provides a unique basis for discussing levels of punishment. The functioning of the legal system has a major impact on society. Empirical data, including statistics, provide a good basis for a wide range of research.